An Overview of Structured Lipid in Food Science: Synthesis Methods, Applications, and Future Prospects - Chi Rac Hong; Byeong Jun Jeon; Kyung-Min Park; Eun Ha Lee; Sung-Chul Hong; Seung Jun Choi (Journal of Chemistry)
Structured lipids have attracted significant interest in industries, such as food, pharmaceuticals, and cosmetics, because they can be alternatives to traditional lipids. Enzymatic synthesis techniques utilizing lipases have gained attention for structured lipids synthesis because of their site and substrate specificity. However, most lipases discovered to date exhibit sn-1,3 regiospecificity or nonspecificity, limiting the selective range of natural oils and fats that can be used as raw materials. In this review, we provide an overview of the current synthesis methods and applications of structured lipids and the limitations of existing lipases in producing structured lipids. In addition, we discuss innovative approaches, including metagenomics, and machine learning, to discover, and classify new lipases and the use of gene editing technologies for lipase engineering. These efforts aim to overcome the limitations of existing lipases and expand the range of natural oils and fats that can be used for the production of structured lipids. Therefore, this study aims to promote a better understanding of structured lipids as a material with high-added value and provides insight into ongoing research efforts in the field.